2005
DOI: 10.1093/bja/aei196
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of bispectral index with end-tidal sevoflurane concentration and age in infants and children

Abstract: In children aged 6 months to 12 yr, the BIS increased paradoxically as ET(sevo) increased from 3.0 to 4.0%. BIS values showed a wide variation in the same ET(sevo) and the age itself was considered to be a factor affecting the BIS values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 21 publications
2
56
0
Order By: Relevance
“…The BIS monitor has been used in children for a long time either during anaesthesia or in ICU. It is unclear, however, if this technology will be as fit for children as for adults [17][18][19][20][21]. We know that it is based on an algorithm developed from adults.…”
Section: Discussionmentioning
confidence: 99%
“…The BIS monitor has been used in children for a long time either during anaesthesia or in ICU. It is unclear, however, if this technology will be as fit for children as for adults [17][18][19][20][21]. We know that it is based on an algorithm developed from adults.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several studies have demonstrated that the BIS and spectral entropy at 1 MAC of sevoflurane (or desflurane) steadily falls from late infancy [28,33,[39][40][41]. The reason for this finding is unclear.…”
Section: Electroencephalogram and Agementioning
confidence: 93%
“…Except the studies which revealed a perplexing association when the sevoflurane concentrations was raised over 3%, all studies investigating the relationship between end-tidal sevoflurane concentrations and BIS values in children demonstrated that these two parameters were inversely proportional in children as they were in adults (5,13,16). We could not identify any studies investigating the relationship between BIS and desflurane in children.…”
Section: Discussionmentioning
confidence: 81%
“…As the development of central nervous system is mostly completed until two years of age, there are many studies suggesting that BIS monitoring may safely be used in children aged over two years (5,(12)(13)(14). Therefore, based on the information in the literature, we included the children who were between 2 and 15 years of age.…”
Section: Discussionmentioning
confidence: 99%